Healing of Wounds Treated with Chitosan Hydrogels with Extracts from Aloe vera and Calendula officinalis - Nakamura-García, Arturo Kenzuke; Santos-Garfias, Elba del Carmen; Alonso-Martínez, Daniela Israeely; Garambullo-Peña, Teresa Itandehui; Covián-Nares, José Fernando; Gómez-Barroso, Mariana; Montoya-Pérez, Rocío (Revista Mexicana de Ingenieria Biomedica, 2022)
This project’s purpose was to evaluate the healing effects of chitosan (CS) hydrogels loaded with extracts from Aloe vera (CS+AV) and Calendula officinalis (CS+CO) on wounds of diabetic and non-diabetic Wistar rats. A total of 24 rats were used; animals were randomly divided into three diabetic and three non-diabetic groups (one control and two treated groups) and monitored for 13 days. A biopsy on the wound site was recovered to assess the collagen and n-acetyl glucosamine content. The wound area ratio was reduced since day 1 on both non-diabetic treated groups. A similar effect was observed on the diabetic group treated with CS+AV, while the diabetic group treated with CS+CO showed a reduction in wound area compared to the diabetic control until day 11 after being wounded. Collagen and n-acetyl glucosamine content were higher in every treated group. Further studies are needed to clarify the underlying mechanisms through which they promote wound healing. These results suggest that the hydrogels prepared are potential material to be used as wound dressings.